2010
DOI: 10.1038/onc.2010.233
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-185 suppresses tumor growth and progression by targeting the Six1 oncogene in human cancers

Abstract: Homeobox genes encode transcription factors that are essential for normal development and are often dysregulated in cancers. The molecular mechanisms that cause their misregulation in cancers are largely unknown. In this study, we investigate the mechanism by which the Six1 homeobox protein, which has a crucial role during development, is frequently deregulated in several poor outcome, aggressive, metastatic adult human cancers, including breast cancer, ovarian cancer, hepatocellular carcinoma and pediatric ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
103
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(109 citation statements)
references
References 24 publications
4
103
0
Order By: Relevance
“…In fact, Mcm10, Hmga1, Igf1r, and Dusp4 were additional targets. miR-185 can target Six1, RhoA, and Cdc42, genes involved in controlling cell cycle progression in various cancer cells (32)(33)(34). Interestingly, although these were not identified in our thymocyte screen, they may play a role in the peripheral Fluo-3 AM-loaded thymocytes were treated with biotinylated (Bio) anti-CD3⑀ and anti-CD4 followed by streptavidin (SA), ionomycin (Iono), and MnCl 2 .…”
Section: Discussionmentioning
confidence: 98%
“…In fact, Mcm10, Hmga1, Igf1r, and Dusp4 were additional targets. miR-185 can target Six1, RhoA, and Cdc42, genes involved in controlling cell cycle progression in various cancer cells (32)(33)(34). Interestingly, although these were not identified in our thymocyte screen, they may play a role in the peripheral Fluo-3 AM-loaded thymocytes were treated with biotinylated (Bio) anti-CD3⑀ and anti-CD4 followed by streptavidin (SA), ionomycin (Iono), and MnCl 2 .…”
Section: Discussionmentioning
confidence: 98%
“…miR-185 was found to suppress glioma cell invasion, indicating that it may be a potential prognostic marker and therapeutic target (16). Previous studies have revealed that miR-185 impedes anchorage-independent growth, cell migration and invasion, in addition to suppressing tumor growth in vivo and increasing cisplatin sensitivity by promoting apoptosis, implicating it as a potent tumor suppressor (17)(18)(19). In the present study, overexpression of miR-185 repressed the growth and invasion of colon cancer cells in vitro and in vivo, which was consistent with the results of previous studies, indicating that miR-185 is a negative regulator of RhoA and Cdc42 and their cellular activities, and can inhibit the proliferation and invasion of CRC cells (20).…”
Section: Discussionmentioning
confidence: 99%
“…The role of PTPN13 in colorectal cancer progression and its regulation by miR-185 need further investigations. In contrast to its oncogenic role, miR-185 has also been demonstrated to suppress tumor growth and progression in non-small lung cancer (34), ovarian, pediatric renal and breast cancer cell lines (35). These findings suggest that miR-185 may target different genes in different cell types, which contributes to different biological processes.…”
Section: Discussionmentioning
confidence: 99%